Uses of 360° video in referees' reflectivity training: Possibilities and limitations - Boyer, Simon; Rochat, Nadège; Rix-Lièvre, Géraldine (Frontiers in Psychology, 2023)
Introduction A pedagogical innovation backed by an online device using 360° video had been devised to train young team sports referees (handball, soccer, rugby) to be more reflective. The objective of this exploratory research was to investigate the ways young student referees use 360° videos in allo-confrontation when carrying out some exercises involving open questions about their viewing experience. Methods Student referees' answers were recorded. A grounded analysis of these answers enabled us not only to identify their main focuses when viewing the 360° videos but also to distinguish different cognitive stances. Results The grounded analysis revealed (1) idiographic differences between student referees in the video sequencing, although the participants seemed to share the same reference points, (2) two kinds of focus, one on the unfolding of the game and another one on the referee peer's activity, and (3) different perspectives according to which student referees use video and to initiate a reflection on a differentiation of several types of immersion: empathetic, simulation, exploratory. Discussion This study highlighted the conditions under which referees' reflectivity was fostered by the use of 360° video during allo-confrontation. Some perspectives for the evolution of 360° video supports for designing training courses for referees are proposed.